2005
DOI: 10.1021/ja055316r
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Crystal Structure of a One-Dimensional Phase of Tetrakis(μ2-benzoato-O,O‘)-bis(dimethyl sulfoxide)dicopper(II)

Abstract: A new crystalline polymorphic phase of tetrakis(mu2-benzoato-O,O')-bis(dimethyl sulfoxide)dicopper(II) was obtained by direct synthesis, in space group P2(1)/n. The copper coordination is in a slightly distorted square pyramidal geometry with an intramolecular Cu...Cu distance of 2.6494(8) angstroms. The Cu-O distances of the two copper in a dimer are different, giving different chemical environments for each Cu ion. The crystal structure is built up of well-separated stacking columns oriented along the b-axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The molecular structure of the title complex is similar to that of tetrakis( 2 -benzoato-O,O')-bis(dimethylsulfoxide)dicopper(II) (Reyes-Ortega et al, 2005) and other related copper complexes (Vives et al, 2003).…”
Section: Structure Descriptionmentioning
confidence: 75%
“…The molecular structure of the title complex is similar to that of tetrakis( 2 -benzoato-O,O')-bis(dimethylsulfoxide)dicopper(II) (Reyes-Ortega et al, 2005) and other related copper complexes (Vives et al, 2003).…”
Section: Structure Descriptionmentioning
confidence: 75%
“…The synthesis of dinuclear and polynuclear complexes for new magnetic materials is still a challenging area of research for inorganic chemists (Kahn et al, 1993;Willet et al, 1985). Among dinuclear species, tetracarboxylate-bridged dimeric copper(II) complexes have been investigated extensively over the past 50 years (Huang et al, 2002;Reyes-Ortega et al, 2005) since the first crystal structure of copper acetate monohydrate was reported by van Niekerk & Schoening (1953). In order to extend the study of this type of dinuclear complex, we report here a new centrosymmetric dinuclear copper complex, (I) (Fig.…”
Section: Commentmentioning
confidence: 94%
“…The title compound was synthesized by direct synthesis, using metallic copper as starting material (Gutié rrez et al, 2001;Reyes-Ortega et al, 2005). The same dinuclear Cu II complex was previously characterized with acetone solvent in place of DMSO (McKenzie & Selvey, 1985).…”
Section: Related Literaturementioning
confidence: 99%
“…effective synthesis of complexes using zero-valent metals, neutral ligands, and polar solvents as starting materials (Gutiérrez et al, 2001). We expect that new molecular arrangements, as well as new compounds including solvent molecules as ligands, may be achieved using such reactions (Reyes-Ortega et al, 2005). We are also interested in the influence of lattice solvents on magnetic properties of paramagnetic coordination compounds.…”
Section: S1 Commentmentioning
confidence: 99%